Characterization of NiO–α-MoO3 Composites Synthesized by Microwave Plasma - Surin Promnopas (Science Faculty of Chiang Mai University, 2019)
Pure orthorhombic MoO3 and NiO–MoO3 composites were successfully synthesized by solid state microwave plasma processing of (NH4)6Mo7O24·4H2O and Ni(NO3)2·6H2O in Ar atmosphere with 3.7 ± 0.1 kPa absolute pressure for 60 min. Phase, morphology, vibration modes and optical properties were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), Raman and Fourier transform infrared (FTIR) spectroscopy, and UV-VIS and photoluminescence (PL) spectroscopy. In this research, formation mechanism of the products was also proposed according to the experimental results.